Homocysteine Restricts Copper Availability Leading to Suppression of Cytochrome C Oxidase Activity in Phenylephrine-Treated Cardiomyocytes - Zuo, Xiao (Public Library of Science, 2013)
Cardiomyocyte hypertrophy induced by phenylephrine (PE) is accompanied by suppression of cytochrome c oxidase (CCO) activity, and copper (Cu) supplementation restores CCO activity and reverses the hypertrophy. The present study was aimed to understand the mechanism of PE-induced decrease in CCO activity. Primary cultures of neonatal rat cardiomyocytes were treated with PE at a final concentration of l00 µM in cultures for 72 h to induce cell hypertrophy. The CCO activity was determined by enzymatic assay and changes in CCO subunit COX-IV as well as copper chaperones for CCO (COX17, SCO2, and COX11) were determined by Western blotting. PE treatment increased both intracellular and extracellular homocysteine concentrations and decreased intracellular Cu concentrations. Studies in vitro found that homocysteine and Cu form complexes. Inhibition of the intracellular homocysteine synthesis in the PE-treated cardiomyocytes prevented the increase in the extracellular homocysteine concentration, retained the intracellular Cu concentration, and preserved the CCO activity. PE treatment decreased protein concentrations of the COX-IV, and the Cu chaperones COX17, COX11, and SCO2. These PE effects were prevented by either inhibition of the intracellular homocysteine synthesis or Cu supplementation. Therefore, PE-induced elevation of homocysteine restricts Cu availability through its interaction with Cu and suppression of Cu chaperones, leading to the decrease in CCO enzyme activity.